Observations on Peer Evaluation using Clickers - Kari-Jouko Räihä; Saila Ovaska; David Ferro (Interaction Design and Architecture(s), 2008)
Clickers and paper forms were used in a senior level HCI class for peer evaluation of student project presentations. Scores given by teachers and students were compared and subjective opinions of students analyzed. Students gave higher scores than teachers and scarcely used the higher and lower ends of the scale. The medium used for evaluation did not have a significant effect on the scores. Students preferred the clickers to paper because of their novelty, possibility of immediate feedback, and easier preservation of privacy. Concerns were raised over lack of individual feedback in the clicker device and limited added value over traditional pen and paper.